Penggunaan Karya Cipta Lukisan Joan Mitchell Pada Katalog Louis Vuitton Sebagai Bentuk Pelanggaran Hak Moral - Lestari, Tika Indah; Haliwela, Nancy Silvana; Balik, Agustina (PATTIMURA Law Study Review, 2025)
Currently, there are still many copyright violations, one of which is the violation of copyright for works of art. Even globally, there are still copyright violations, as experienced by a well-known painter in the field of American art and graphics whose injury was used as a backdrop for the catalog of one of the well-known brands, namely Louis Vuitton. The painting was used without permission from the copyright holder. Not only that, Louis Vuitton also did not mention the name of the creator when using Joan Mitchell paintings. According to the law in force in Indonesia, painting is a branch of fine art whose existence is protected as stated in Article 40 Paragraph (1) letter f of the law number 28 of 2014 concerning copyright.